2017
DOI: 10.1507/endocrj.64.s47
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin treatment improves physical decline in sarcopenia model mice through muscular enhancement and mitochondrial activation

Abstract: Chronic kidney disease (CKD) impairs physical performance in humans, which leads to a risk of all-cause mortality. In our previous study, we demonstrated that a reduction in muscle mitochondria rather than muscle mass was a major cause of physical decline in 5/6 nephrectomized CKD model mice. Because ghrelin administration has been reported to enhance oxygen utilization in skeletal muscle, we examined the usefulness of ghrelin for a recovery of physical decline in 5/6 nephrectomized C57Bl/6 mice, focusing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…These effects presumably would mirror those of ghrelin demonstrated in several preclinical cachexia and muscle atrophy models and in cachectic patients with heart failure and chronic obstructive pulmonary disease [83] , [85] , [86] , [87] , [88] , [89] . Notably, in a mouse model of chronic kidney disease, ghrelin administration was shown not only to improve muscle strength and to increase skeletal muscle mitochondria-related gene expression but also to improve exercise endurance [82] , [90] . Many details regarding these latter effects of ghrelin remain unclear; interestingly, both the acyl and unacyl forms of ghrelin have been shown to mediate some of these effects [85] , [91] and GHSR expression has been detected in skeletal muscle in some but not all studies [82] , [91] , [92] , [93] , [94] .…”
Section: Discussionmentioning
confidence: 99%
“…These effects presumably would mirror those of ghrelin demonstrated in several preclinical cachexia and muscle atrophy models and in cachectic patients with heart failure and chronic obstructive pulmonary disease [83] , [85] , [86] , [87] , [88] , [89] . Notably, in a mouse model of chronic kidney disease, ghrelin administration was shown not only to improve muscle strength and to increase skeletal muscle mitochondria-related gene expression but also to improve exercise endurance [82] , [90] . Many details regarding these latter effects of ghrelin remain unclear; interestingly, both the acyl and unacyl forms of ghrelin have been shown to mediate some of these effects [85] , [91] and GHSR expression has been detected in skeletal muscle in some but not all studies [82] , [91] , [92] , [93] , [94] .…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin may be a promising therapeutic target for sarcopenia due to its positive effects on gastric motility, food intake, and growth hormone secretion. A previous study indicated that ghrelin treatment could effectively reduce the physical decline in sarcopenic mouse model through muscular enhancement and mitochondrial activation 105. Moreover, a clinical study suggested that ghrelin administration could improve left ventricular function and exercise capacity, and increase muscle strength and lean body mass in patients with CHF 106.…”
Section: Treatmentsmentioning
confidence: 99%
“…110) Using human proximal tubular cells, a DPP-4 inhibitor showed the cell protective activity without the action of GLP-1. 111) Taking these findings into consideration, a DDP-4 inhibitor may exert cytoprotective activities not only inhibiting the degradation of GLP-1 but also via its direct action. 5.5.…”
Section: Ast-120mentioning
confidence: 99%